Off-label use of oncology drugs: national survey results - Eva González-Haba Peña; María José Agustín Ferrández; Irene Mangues Bafalluy; Nicolás Alfredo López; María Dolores Fraga Fuentes; Roberto Marín Gil; María José Martínez Bautista; María José Martínez Bautista; María José Martínez Bautista; Ana Clopés Estela (Elsevier, 2015)
Purpose: identify by means of a survey the off-label treatments more often used in the oncohaematology area, as well as to know the established procedures and criteria used to authorise those treatments. Methods: a four-section survey was designed: 1) demographic data and hospital activity, 2) Off-label treatments protocol, 3) Approval criteria and 4) Off-label oncology treatments conducted during the last year. Results: in 42.1% of the hospitals it's needed an authorisation before dispensing in more tan 80% of the treatments. The most influential factor in the approval-dispensation system is the available evidence. The consent of the hospital management with previous Pharmacy department's report was the most common authorisation procedure. 55.3% of the hospitals settled specific patient criteria to help the decision-making altogether with the available safety and efficacy data of the drug for the requested indication. In most centers a lower level of evidence is accepted if there are no therapeutic alternatives as well as in tumors of low prevalence. Most of the centers have not clearly established a criterion of effectiveness to consider a benefit as clinically relevant, nor the cost-effectiveness threshold for approving a FFT. Conclusions: there is a great variability in the off-label treatments use and also in the criteria used for its approval.